The Sacred and Secular Canon in Romanticism - Jasper, D. author. aut Link
X, 158 p.
Keywords: This book is an interdisciplinary study of Romanticism which focuses on the reception of the Biblical canon in poetry, art and theory. The Bible is acknowledged as the heart of European culture, but as its status as the sacred text of Judaism and Christianity becomes questionable, it remains at the turning-point between sacred and secular art in the modern world. The insights of Romanticism are crucial for our understanding of postmodernism as a fundamentally religious movement which acknowledges both the death and rebirth of religious language.